A field study on a sample of adolescents in the county of M’sila - himeur, saida; baaziz, ibrahim (Journal of Social Sciences and Humanities, 2021)
The study aimed to reveal the nature of Recreational usesof the YouTube site and its various purposes and contents by the Algerian teenager, especially with the changes taking place in making videos and their forms, In exchange, the change of the individual social life structure.We used the analytical descriptive method and the questionnaire tool that was applied to a sample of 193 individuals, chosen deliberately. The study concluded a number of results, which the most important are:the use for entertainment and leisure is in the first ranking and scientific research is in the second ranking. it figured out that movies and comedy series are in the first order and then the music videos.There is a statistical correlation between the rates of using YouTube site for recreation and academichievement.